INSECTS OF THE GENUS LETOPALOPTERA O. MART. (INSECTA: HYPOPERLIDA: LETOPALOPTERIDAE) FROM THE UPPER PERMIAN SOYANA LOCALITY - Novokshonov V.G.; Willmann R. (My University, 2002)
Distinctive long-legged insects Letopaloptera carpenteriana O. Martynova, 1961, and L. albardiana O. Martynova, 1961, from the Kazanian of the Soyana locality in the Arkhangel'sk Region are redescribed. The data on their morphology are corrected and supplemented.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская